Perawatan Diagnostik dan Konservatif Hidropneumotorax karena Tuberkulosis pada Anak Laki-Laki Berusia 17 Tahun - Abed Nego Okthara Sebayang (Scripta Score Scientific Medical Journal, 2020)
Background: Pulmonary tuberculosis is an infectious disease of the lungs caused by Mycobacterium Tuberculosis. The prevalence of pulmonary tuberculosis in Indonesia is estimated at 420,000 every year. Pulmonary tuberculosis is transmitted from person to person through droplet infection. Complications that can occur in pulmonary tuberculosis are empyema, pleural effusion, hydropneumothorax and even fibrothorax.